OP95 Easy language for a complex problem: a qualitative study of goal setting interactions between people with chronic conditions and their healthcare providers. (13th September 2016) - Franklin, M; Willis, K; Lewis, S; Smith, L; Hughes, S; Rogers, A
Abstract : Background: The management of the rise of chronic conditions is a focus of contemporary public health policy which seeks to reduce both the economic burden of ill health and to improve quality of life for people living with chronic conditions. In many western countries collaborative goal setting is promoted as a strategy to support self-management, yet there are often disparities in the goals of healthcare providers (HCPs) and people with chronic conditions. There is a need to improve our understanding of the relational nature of goal setting which is shaped by social and contextual factors. This study examines the language used in interactions between people with a chronic condition (e.g. COPD, T2DM, obesity) and their HCPs to improve our understanding of how goals are set in the context of self-management support. Methods: A qualitative study of 20 cases, each including an observation of a consultation and follow up interview with people with a chronic condition and their HCP were conducted. Participants were purposively sampled to include a range of HCPs and people with a chronic condition, in New South Wales, Australia. HCPs and people with a chronic condition were interviewed about their perception of the interaction, the notion of chronic condition self-management and goal setting specifically. Observations and interviews were digitally recorded and transcribed. Data were analysed thematically to identify patterns of goal setting and language used. Results: Goal setting occurred within a context that privileged individual responsibility. Language of hope permeated the interactions however it was tempered by messages of morality (e.g. the 'right' choices). The central themes evident in the data included the 'giving of goals', 'simplicity and ease of behaviour change'; 'being held to account'; and 'directive advice rather than problem solving'. HCPs remained directive in goal setting and this approach appeared to negate the social context that people with chronic conditions brought to the interaction. Conclusion: Despite the intent of collaborative goal setting the language used by HCPs remains directive and reductive. Such use of language is powerful and provides little space for people with chronic conditions to negotiate their goal preferences. An opening up of language may provide the support needed to engage in self-management. This study makes a contribution to improving our understanding of the goal setting process and its relationship with self-management.